Revolutionizing Food and Space. (August 2014) - Efird, Rob; Allen, Will
Anthropologist Rob Efird interview urban agriculture innovator Will Allen, who discusses his recent book The Good Food Revolution, the challenges and potential of intensive urban agriculture and the historical background of our broken food system.